Use of a Gonadotropin-Releasing Hormone Agonist to Manage Perimenopausal Women With Symptomatic Uterine Myomas - Peng-Hui Wang; Wen-Ling Lee; Ming-Huei Cheng; Ming-Shyen Yen; Kuan-Chong Chao; Hsiang-Tai Chao (Elsevier, 2009)
Objective: To determine the acceptability and effectiveness of a gonadotropin-releasing hormone (GnRH) agonist for the treatment of perimenopausal women with symptomatic uterine myomas. Materials and Methods: The participants included 43 women with symptomatic myomas who wished to retain their uteri. All the women were older than 45 years old, agreed to use the GnRH agonist for menopause induction, and were without any underlying malignancy. They were treated with six courses of GnRH agonist between 2004 and 2005. The definition of re-intervention included: (1) surgical intervention, such as hysterectomy, myomectomy or laparoscopic uterine vessel occlusion, or (2) modification of GnRH agonist use. Modification of GnRH agonist use included either failure to complete a 6-month GnRH agonist treatment course, or re-use of GnRH agonist with/without interruption of continuity. Failure was defined as women who underwent surgical intervention or failed to complete the 6-month GnRH agonist treatment. Evaluations were performed every 6 months, for up to 2 years. Results: Re-intervention rates were 14.0% (n = 6), 23.3% (n = 10) and 32.6% (n = 14), and failure rates were 7.0% (n = 3), 11.6% (n = 5) and 16.3% (n = 7), at the end of the 6-, 12- and 24-month follow-up periods, respectively. Three patients failed to complete the 6-month GnRH agonist treatment, and four received surgical interventions. Conclusion: More than 80% of women in this study benefited from the use of GnRH agonist to produce menopause, suggesting that this can be an alternative choice for managing perimenopausal women with symptomatic uterine myomas.